Tren Kajian Kewirausahaan Sosial Pada Tahun 2017-2022 - Rosmiati, Rosmiati; Kurniadi, Romi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The Efforts to align the business world with social values are the main challenge for observers and actors of social entrepreneurship. The development of entrepreneurship education is one of the efforts made by academics in fostering the character of social entrepreneurship. This study aims to reveal the trend of social entrepreneurship studies. The method used is bibliometric analysis of social entrepreneurship research articles in 2017-2022 on the Google Scholar database through the Publish or Perish application. The data is analyzed based on the number of publications, the number of citations, and the number based on the publisher. The data was visualized through a keyword approach using the VoS Viewer application. The results showed taht topics of social value, social entrepreneurship education, non-governmental organizations, and tourism emerged as trends that have high potential for further study. Providing social entrepreneurship education with social value content as the main driver of NGO and tourism-based entrepreneurial activities is an interesting study recommendation to be carried out in the future.